Sikap Konsumen Pada Toko Daring Produk Fesyen di Indonesia - Ardhiyansyah, Andri; Nugroho, Sahid Susilo (Universitas Nusa Putra, 2020)
The development of technology at this time can facilitate someone in finding the product they want. This is because the availability of information, and access services that can allow someone to get what they want. Fashion products become the influence of various industries, because in the present day someone wants to look neat and fashionable, therefore there are many online businesses with fashion products that exist in Indonsesia. The development of online fashion products can not be separated from the quality of websites that offer convenience, completeness of products and information about products online. However, there are constraints in shopping online that consumers can not feel and see the product directly. Consumers can only read product information through online catalogs and read comments by previous consumers. The purpose of this study is to determine consumer attitudes in online shopping with the quality of websites, electronic worth of mouth, perceived benefits and consumer trust in shopping online. This study uses 220 respondents who have been shopping for fashion products online with purchases less than six months and spread throughout the territory of Indonesia. Data testing is done by using SEM with AMOS software. The findings show that not all the variables tested have significant and expected results. Electronic worth of mouth of the beliefs and perceived benefits in consumer attitudes of online shopping is not significant. This is because, this research is a research attitude toward behavior. It will be difficult to measure the consistency of one's behavior to stay the same between one behavior and another.